2015
DOI: 10.5902/1980509819616
|View full text |Cite
|
Sign up to set email alerts
|

Perdas De Solo, Água E Nutrientes Por Erosão Hídrica Em Uma Estrada Florestal Na Serra Catarinense

Abstract: RESUMOO uso do solo influencia a erosão hídrica, sendo que, em geral, em estradas dentro de áreas reflorestais são altas as perdas de solo, água e elementos químicos. O trabalho objetivou quantificar as perdas de solo, água e elementos químicos causadas pela erosão hídrica durante 17 meses, sob chuva natural, em uma estrada dentro de uma área de reflorestamento de pinus. O estudo foi realizado no município de Campo Belo do Sul -SC, na Florestal Gateados Ltda., em um solo Nitossolo Háplico típico. Para a coleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 1 publication
(3 reference statements)
0
3
0
5
Order By: Relevance
“…These results agree with those of Gómez et al (2009) also observed losses of water soluble K that were nearly 5.3 times greater than the losses of P in water. In this study, a possible explanation for the high losses of potassium in the runoff, compared to the phosphate losses, is that the study was done in a Typical Acric Red-Yellow Latosol with a very clayey texture, where the phosphorus is strongly adsorbed to the sediments (Ker, 1995), together with the fact that K is more soluble and mobile in the soil compared to P (Oliveira et al, 2015). From an environmental point of view, the low phosphorus loss in water, combined with the fact that this is a limiting factor for triggering the eutrophication of waters, mean that in this study, such environmental damage to the water resources was reduced due to the class of soil studied (Latosol).…”
Section: Resultsmentioning
confidence: 99%
“…These results agree with those of Gómez et al (2009) also observed losses of water soluble K that were nearly 5.3 times greater than the losses of P in water. In this study, a possible explanation for the high losses of potassium in the runoff, compared to the phosphate losses, is that the study was done in a Typical Acric Red-Yellow Latosol with a very clayey texture, where the phosphorus is strongly adsorbed to the sediments (Ker, 1995), together with the fact that K is more soluble and mobile in the soil compared to P (Oliveira et al, 2015). From an environmental point of view, the low phosphorus loss in water, combined with the fact that this is a limiting factor for triggering the eutrophication of waters, mean that in this study, such environmental damage to the water resources was reduced due to the class of soil studied (Latosol).…”
Section: Resultsmentioning
confidence: 99%
“…According to the Köppen classification (1948), the climatic type of the Santa Catarina Plateau region is a transition between Cfa (wet mesothermic, with no defined dry season, hot summers, with rare occurrence of frost in winter) and Cfb (mesothermic wet, with no defined dry season, fresh summers, with severe and frequent frosts occurring in winter), with temperatures varying from 13°C to 25°C and rainfalls distributed throughout the year, totaling an average of 1841 mm annually (Oliveira, Bertol, Barbosa, Campos, & Mecabô Junior, 2015). As for the soil, they are shallow and stony, with low fertility and little suitable for annual crops with some obstacles from the undulating and gently undulating soils, more suitable for crops; being predominant the latosols and tropohumult in the less steep areas and lithosols and neosols in more rugged areas (Embrapa, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Os eventos de chuva acumulados foram considerados como repetições, da mesma forma que nos estudos de Cavichiolo (2005) e de Oliveira et al (2015), pois os eventos de chuva tiveram a mesma intensidade, duração e quantidade para cada sistema de drenagem no período de avaliação.…”
Section: Análise De Dadosunclassified
“…A falta ou uso inadequado de técnicas de construção e manutenção de estradas (KELLER; SHERAR, 2010), a ineficiência ou ausência de sistemas de drenagem (OLIVEIRA et al, 2015) e o tráfego de veículos pesados, principalmente, nas atividades de colheita e transporte (CORRÊA; DEDECEK, 2009), potencializam os processos erosivos, tornando as estradas as principais responsáveis pela produção de sedimentos em áreas florestais (OLIVEIRA et al, 2010), ou um dos principais usos produtores de sedimentos em bacias hidrográficas florestais (RODRIGUES et al, 2018).…”
unclassified